2014
DOI: 10.1111/jpc.12601
|View full text |Cite
|
Sign up to set email alerts
|

Severe group A streptococcal infections in a paediatric intensive care unit

Abstract: Invasive GAS disease in children may cause severe multi-organ failure with resultant prolonged intensive care stay and significant morbidity. However, a high rate of survival and return to normal functioning may be achieved with multi-system intensive care support and multi-disciplinary rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
2
16
0
2
Order By: Relevance
“…All the patients who had ECMO also received clindamycin, IVIG and steroids in addition to standard antibiotics. There are limited data on the use of ECMO in TSS with one report of an adult with TSS-induced heart failure and a paediatric series of severe group A streptococcal infections from our institution 18 19. All these reported cases survived.…”
Section: Discussionmentioning
confidence: 99%
“…All the patients who had ECMO also received clindamycin, IVIG and steroids in addition to standard antibiotics. There are limited data on the use of ECMO in TSS with one report of an adult with TSS-induced heart failure and a paediatric series of severe group A streptococcal infections from our institution 18 19. All these reported cases survived.…”
Section: Discussionmentioning
confidence: 99%
“…14,28,35 The fatality rate associated with STSS and necrotizing fasciitis was 36% (4/11) and 38% (5/13), respectively. This underscores the highly-specific fatality rate caused by these two conditions, similar to what has been observed by Johansson, who described a 67% STSS fatality rate, compared to 4.9% among those who did not have STSS.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,11,13,35 Also, in this study the time elapsed between the onset of symptoms and the introduction of treatment with adequate antibiotics was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies on critically ill patients with iGAS in the ICU are scarce, studies on all patients admitted to a hospital with iGAS are more common. Mortality in all patients with GAS infection has previously been reported to be 8-23% in the rst 7 days (7,29). Two studies have reported mortality rates of 38-40% in patients with iGAS admitted to the ICU (30,31).…”
Section: Discussionmentioning
confidence: 99%